Notch Signaling Ligand Jagged1 Enhances Macrophage-Mediated Response to Helicobacter pylori - Wen, Junjie; Chen, Chuxi; Luo, Meiqun; Liu, Xiaocong; Guo, Jiading; Wei, Tingting; Gu, Xinyi; Gu, Sinan; Ning, Yunshan; Li, Yan (Frontiers in Microbiology, 2021)
Helicobacter pylori (H. pylori) is one of the gram-negative bacteria that mainly colonize the stomach mucosa and cause many gastrointestinal diseases, such as gastritis, peptic ulcer, and gastric cancer. Macrophages play a key role in eradicating H. pylori. Recent data have shown that Notch signaling could modulate the activation and bactericidal activities of macrophages. However, the role of Notch signaling in macrophages against H. pylori remains unclear. In the present study, in the co-culture model of macrophages with H. pylori, the inhibition of Notch signaling using γ-secretase decreased the expression of inducible nitric oxide synthase (iNOS) and its product, nitric oxide (NO), and downregulated the secretion of pro-inflammatory cytokine and attenuated phagocytosis and bactericidal activities of macrophages to H. pylori. Furthermore, we identified that Jagged1, one of Notch signaling ligands, was both upregulated in mRNA and protein level in activated macrophages induced by H. pylori. Clinical specimens showed that the number of Jagged1+ macrophages in the stomach mucosa from H. pylori-infected patients was significantly higher than that in healthy control. The overexpression of Jagged1 promoted bactericidal activities of macrophages against H. pylori and siRNA-Jagged1 presented the opposite effect. Besides, the addition of exogenous rJagged1 facilitated the pro-inflammatory mediators of macrophages against H. pylori, but the treatment of anti-Jagged1 neutralizing antibody attenuated it. Taken together, these results suggest that Jagged1 is a promoting molecule for macrophages against H. pylori, which will provide insight for exploring Jagged1 as a novel therapeutic target for the control of H. pylori infection.